Enhancing Community Engagement Through Social Media: Analyzing Its Role in Promoting Sustainable Ecotourism and Economic Development in Alas Purwo National Park - Aniyati, Ika; Martini , Ida Ayu Oka (International Journal of Economics Development Research (IJEDR), 2024)
Alas Purwo National Park (TNAP), located in Banyuwangi, East Java, Indonesia, is an important area in natural resources conservation. With its extraordinary diversity of flora and fauna, TNAP has great potential for sustainable ecotourism development. In 2016, TNAP was designated as part of the World Biosphere Reserve and joined the Blambangan Biosphere Reserve with Mount Ijen and Baluran National Park. One of the main attractions in TNAP is Savana Sadengan, an artificial savanna used for grazing various types of animals, where visitors can see wild animals gathering for food. G-Land Beach, famous for its high waves, is a popular surfing location, with its waves being the second highest after Hawaii. The development of ecotourism in Alas Purwo requires active involvement from the community to increase understanding of the importance of environmental conservation as well as effective promotion to attract tourists. Social media plays an important role in facilitating promotion and education about ecotourism, and can encourage community participation in nature management and conservation. This study aims to analyze the role of social media in ecotourism promotion and community involvement in Alas Purwo National Park, using SWOT analysis to evaluate internal and external factors that influence the success of ecotourism development. The results show that social media has a very important role in increasing community awareness, promotion and participation. However, there are some challenges related to limited network and transportation infrastructure, as well as the need for technology education among local communities. Based on the SWOT analysis, the strategy for developing sustainable ecotourism in TNAP must consider the strengths and opportunities that exist, while overcoming the weaknesses and threats faced. Thus, it is hoped that TNAP can become a major destination for ecotourism and contribute to conservation and environmental preservation, which ultimately brings benefits to the environment and surrounding communities.